Ukrainian Community Archives in Victoria, Australia: A Stocktake - Achilli, Alessandro; Pavlyshyn, Marko; Shmihelska-Kozuliak, Olha (East/West, 2023)
Contemporary research increasingly recognizes the role of community archives in preserving evidence of the pasts of identity groups, validating their historical experience, and thus furthering the goals of social justice and equality. Such values underlie the Association of Ukrainians in Victoria (Australia) Archival Project, which the present article places into the broader context of Ukrainian community archival collections in the state of Victoria. Data obtained through interview have enabled a descriptive survey of such collections, which are found to be concentrated in a handful of “archival clusters” in suburban Melbourne and regional Victoria. The most typical contents of the collections—records of the proceedings and activities of community secular and religious organizations—reflect the dominant role in the community’s life of organizations established by post-World War II immigrants. The collections constitute a rich resource for research into the part of the community encompassed by these organizations, even if, as a rule, at least at present, they are not well ordered or described. They are less revealing of the experience of immigrants who arrived later or were less inclined to join community organizations. Lack of resources, both human and material, confronts the mainly volunteer officeholders who are responsible for the organizations’ archives. In consequence, collections are often inadequately and sometimes unsafely housed, and in general only informally organized; finding aids or descriptions of them are seldom available. Initiatives taken by some organizations suggest that there is growing awareness among community activists of the potential value of archives for showing and interpreting the community to itself and to others.